PENGEMBANGAN E-COLLECTING MODULE BERBASIS WEB BAGI TARUNA PROGRAM STUDI LALU LINTAS UDARA POLITEKNIK PENERBANGAN SURABAYA - Syahrul Harry Ramadhan; Dewi Ratnasari; Dani Chandra Yudo Pranoto (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Polytechnic Aviation of Surabaya is one of the educational institutions under the Human Resources Agency Development of Transportation. During the Covid pandemic that is currently hitting the world, educational institutions conduct online learning to prevent the spread of the covid virus, including what was done by the Polytechnic Aviation of Surabaya. In online learning, the material is presented online. Likewise, the teaching materials used are also softfiles. The above phenomenon is also supported by the progress of the 21st century world which is marked by the development of increasingly sophisticated communication information technology in various fields, including education. Where many activities are shifted to online in order to facilitate human work. The main problem of this research is the development web-based e-collecting module cadets of air traffic controller. The purpose of the research conducted by the author is as one of the requirements for obtaining the title of Associate Expert Degree (A.Md) in the Diploma III Air Traffic Control at the Polytechnic Aviation of Surabaya. Development web-based e-collecting module contains modules and other supporting documents for cadets air traffic study programs. Users can at any time download modules in the form of softfiles to be used in learning. This makes it easier for cadets to get modules and other document in online learning. Therefore, the authors take in general from the series of research that has been carried out, namely the development web-based e-collecting module as a place for cadets for air traffic study programs to get teaching materials and other documents that can be accessed anytime and anywhere for use in learning.